Sistem Pembayaran Hasil Cetak Printer Berbasis Mikrokontroler dan Near Field Communication (NFC) - Novira Desry Anggy; Ratna Aisuwarya (Universitas Andalas, 2021)
The print-out price for printer services varies according to the density of the paper and the amount of ink used, and the payment is made manually by calculating the total print output. Therefore a system is created that can display rates and total invoices automatically based on time printed, as well as automatic payments that make it easier for service providers and service users. The design of this system consists of Arduino mega, ESP8266, relay, Near Field Communication (NFC), and printer. This system can distinguish the print price rates according to the time of printing, the time span of printing and the tariff is Rp. 300.00 with a printing time of 1-6 seconds, Rp. 500.00 with a time of 7-13 seconds, and finally Rp. 700, 00 with a time span above 14 seconds. The success rate of this system in classifying print tariffs is 95%.